Cognition and Brain Activation in Response to Various Doses of Caffeine: A Near-Infrared Spectroscopy Study - Zhang, Bin; Liu, Ying; Wang, Xiaochun; Deng, Yuqin; Zheng, Xinyan (Frontiers in Psychology, 2020)
Caffeine, which is widely used for enhancing athletic performance, has been suggested a positive impact on cognition via stimulating the brain. However, no study published to date has explored the effects of different doses of caffeine ingestion on brain activation via cortical hemodynamics. The purpose of the present cross-over, double-blind study was to investigate the effects of low, moderate, and high doses of caffeine ingestion on cognitive performance and brain activation. Ten healthy male subjects ingested placebo or caffeine (3, 6 or 9 mg/kg body mass). The effects of each treatment condition were evaluated by Stroop tasks before and 60-min after the ingestion of caffeine. Reaction time (RT) and accuracy of responses to congruent and incongruent stimuli were assessed. As an index of brain activation with cognition, levels of oxygenated hemoglobin (HbO) were measured via near-infrared spectroscopy. A 4 × 2 mixed ANOVA revealed that there were significant interaction effects for RT in both incongruent and congruent conditions (P < 0.01, Pη2 = 0.384 and P < 0.05, Pη2 = 0.259 and P < 0.05, Pη2 = 0.309, respectively). Both 3 and 6 mg/kg caffeine ingestion significantly decreased RT to incongruent stimuli. The only dose of caffeine to decrease RT in response to congruent stimuli was 3 mg/kg. None of the doses of caffeine administered affected accuracy of responses to incongruent or congruent stimuli. Under the congruent stimulus condition, ingestion of 3 mg/kg caffeine significantly increased mean HbO in dorsolateral prefrontal cortex, frontal pole area, ventrolateral prefrontal cortex (P < 0.01, Pη2 = 0.319, P < 0.05, Pη2 = 0.263, and P < 0.05, Pη2 = 0.259, respectively). None of the doses of caffeine investigated affected HbO under the incongruent stimulus condition. Ingestion of low dose caffeine has greater effects on cognition and brain activation than moderate and high doses of caffeine, suggesting that low-dose caffeine may be a selective supplement in enhancing executive function and prefrontal activities.